Humans versus nature : a global environmental history - Headrick, Daniel R. (New York : Oxford University Press, 2020)
"This book is about the ongoing conflict between humanity and the natural environment. Over the past 200,000 years, humans have multiplied and populated the Earth. When they domesticated plants and animals and replaced foraging with agriculture and herding, they depleted natural resources, deforested the land, and caused mass extinctions. But nature has agency too, causing pandemics of plague, smallpox, measles, influenza, and other diseases and a climate change called the Little Ice Age. In recent centuries, industrialization has accelerated extinctions, deforestation, and resource depletion, even in the oceans. Twentieth-century developmentalism and mass consumerism have caused global warming and other climate changes. Environmental movements have argued for the need to mitigate the negative consequences of technological and economic change. The future of humanity and the Earth depends on choices between achieving a sustainable balance between humans and nature, carrying on as before, or learning to manage the biosphere. environment, mass extinction, domestication, agriculture, pandemic, industrialization, developmentalism, consumerism, global warming"--
The foragers -- Farmers and herders -- Early civilizations -- Eurasia in the classical age -- Medieval Eurasia and Africa -- The invasion of America -- The transformation of the old world -- The transition to an industrial world -- The West and the non-West in the nineteenth century -- War and developmentalism in the twentieth century -- Peace and consumerism in the twentieth century -- Climate change and climate wars -- Plundering the oceans -- Extinctions and survivals -- Environmentalism.
Includes bibliographical references and index.
Keywords: Nature -- Effect of human beings on; Global environmental change -- History